Perancangan Dan Penerapan Manajemen Risiko Pada Cv. Comformindo Untuk Menjadi Bisnis Berkelanjutan - Candy Candy; Kellen Vincent (Universitas Internasional Batam, 2021)
The efforts to achieve the company's vision and mission don't always go according to plan, that's because there are problems or risks that arise suddenly. The company's inability to reduce or manage the uncertainty or risk will have a significant effect to the efforts in achieving the company's goals and the emergence of inherent risk and risidual risk, especially in pandemic conditions. CV. Comformindo has never designed and implemented a risk management system into the company's operational activities due to a lack of insight and awareness of the importance of risk management. From this case, the CV. Comformindo needs to be assisted in getting to know about risk management and assisted in designing a risk management system that is suitable for the operational activities of CV. Comformindo at this time. The information was collected using interview and observation methods, while the risk management system design was made with the help of Microsoft Office software. After the risk management system design is implemented by CV. Comformindo, it can be concluded that there has not been any significant benefit in the short term, but CV. Comformindo already has awareness and insight regarding the importance of risk management, this is also a first step and also an important point to become a sustainable business. The suggestion for the next practical work related to risk management is to invite partners to practice a real risk management system rather than just providing a theory related to risk management.